Knowledge Devotee Gregory G. Maskarinec: Dhaulagiri Journal, and Me - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2023)
This paper focuses on my perception and memories of Professor Gregory Maskarinec, who passed away on June 16, 2022, at 71. Professor Maskarinec was a member of the International Advisory Board of the Dhaulagiri Journal of Sociology and Anthropology. He was also an author, reviewer, and financial endower. This paper discusses how Professor Maskarinec contributed to promoting journal publication and knowledge dissemination in the field of social sciences in Nepal. The paper aims to highlight the author's perception of devotion to the production and sharing of knowledge, encouragement and promotion to young scholars, and generosity for knowledge production and sharing. Despite limited interactions, I observed some crucial points that I could highlight about his nature and worldview. The information presented here is from my observation, exchanged emails, interviews, papers, field notes, and contributions to the Dhaulagiri Journal of Sociology and Anthropology. Professor Maskarinec has shown big lessons and a path for social sciences research scholars. He taught us the importance of having contact with the research subjects. I admire the simplicity of his life and his harmonious relationship with people of different social, cultural, linguistic, and religious identities. These behaviors are based on the cultural relativism that Professor Maskarinec possessed. I strongly felt that Professor Maskarinec was observing his death closely. As he noticed he was dying soon from cancer, he focused his valuable time on the most important spiritual actions. Maskarinec was familiar with Nepali customs and rituals that can be performed before and after the final departure of life. In my understanding, a financial endowment he provided to the Dhaulagiri Journal was a part of the ritual of dan (donation). He had also requested his close friend to perform rituals at Pasupati temple in Nepal. The conclusion is that we must follow a scholarly path, which is deeply engaged with the topics and subjects and respectfully committed to knowledge sharing.